Research of collective sport games in the field of kinesiology and sport science in the world and in Croatia - Pavicic, L.; Lozovina, M.; Lozovina, V. (Acta Kinesiologica, 2014)
Choosing a representative scientific papers in four collective sports games (water polo, basketball, handball and football), we tried to elucidate the conceptual and methodological approaches to domestic and foreign authors-scientists in studying the phenomenon of group games. Different schools (English, French German and Croatian) have different concepts or very similar methodologies. Their common feature is that their analysis is always partial, never comprehensive, and from such analysis and could not arise models required and necessary for the training of the above collective sports games. We assume that the reason for this "slavery" equation specifications sporting activities, especially in Croatian authors. We believe that the need for new scientific paradigm in the study of collective sports games because previous studies have not offered sufficient and insufficient for optimal modeling of collective sports games.